PENGGUNAAN AUGMENTED REALITY UNTUK MEMFASILITASI PERUBAHAN REPRESENTASI KONSEPTUAL SISWA TENTANG SISTEM PERNAPASAN DAN KEMAMPUAN BERPIKIR KREATIF - Annisa Syafigha Putri, - (2020)
Augmented Reality (AR) is an appropriate technology in education that can visualize object into reality. In biology, the concept of respiratory system includes concrete and abstract concept such as biological process that cannot observed directly. AR can facilitate students' understanding to the abstract concepts. The purpose of this study was to identify the use of AR in facilitating students' representation conceptual change about respiratory system and their creative thinking skills. This study used the Quasy Experimental Design method with the design Non-Equivalent Control Group Design. The sample consisted of 30 students in experimental class and 30 students in control class. The implementation learning in the experimental class use AR by scanning the markers provided in worksheet and in the control class carried out learning by using power point. The data was collected using essay item test given before and after learning to measure change of the conceptual representation and each indicator of creative thinking skill. The analysis of students' representation conceptual change is based on the type and level of representation as well as the accuracy and depth of concept. The result of the study showed that AR can facilitate type and level of representation change. The experimental class showed better accuracy and depth of concept comparing the control class. Type of representation change which was dominated by text in pretest, change into text & pictures in posttest. Level of representation change which was dominated by macroscopic level in pretest, change into microscopic level in posttest. The result of t test for creative thinking skill showed significant difference between experimental and control class. This study suggest that using AR can affect student creative thinking skill.